Transport Infrastructure and Regional Integration in the Middle East - El-Anis, Imad (The Muslim world, 2021)
The soft aspects of the infrastructure of regionalism in the Middle East have previously been studied, while the impact of the region’s hard infrastructure, in particular transport infrastructure, has received little attention. This paper contributes to the study of regionalism in the Middle East by investigating the relationship between hard infrastructure and economic integration. It analyzes whether the state of domestic and cross-border transport infrastructure in the region promotes regional trade. This is done by addressing the following sub-questions: 1) What is the condition of domestic and cross-border transport infrastructure in the Middle East? And 2) What is the relationship between domestic and cross-border transport infrastructure and regional trade in the Middle East? These questions are answered by examining Egypt, Iraq, Israel, Jordan, Lebanon, Palestine, Syria, and Turkey as representative samples of the broader region. It is argued that regionalism relies on the development of domestic and cross-border transport infrastructure and where the latter is limited, regionalism cannot deepen. The study concludes that domestic and cross-border transport infrastructure performance is weak in several of the countries studied and that this weakness hinders regional economic integration regardless of the level of the region’s soft infrastructure.